Peran E-Commerce dalam Transformasi Digital UMKM Indonesia: Sebuah Kajian Literatur - Selly Silviawati; Eka Satria Wibawa; Nindi Anggi Wardani; Sri Wahyuning; Ita Noviana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to examine how e-commerce supports the digital transformation of MSMEs in Indonesia, with particular emphasis on social, cultural, and organizational dimensions. The research focus arises from the growing adoption of e-commerce following the COVID-19 pandemic, despite the fact that MSMEs continue to face major obstacles such as limited digital literacy, infrastructure gaps, and weak competitiveness. A qualitative approach with a collective case study design was employed to capture real experiences as well as the meanings constructed by business actors. Data were collected through semi-structured interviews, participant observation, and document analysis involving 15 MSMEs located in Jakarta, Surabaya, and Yogyakarta, complemented by insights from MSME associations and local government representatives. The data analysis combined thematic methods with Miles & Huberman’s interactive model to identify deeper patterns. The findings highlight three central themes: first, e-commerce is perceived not only as a tool for modernizing businesses but also as a means of gaining social legitimacy; second, adaptation strategies evolve through improvisation, family support, and community-based learning; and third, the success of digital transformation is strongly influenced by external factors, particularly the role of associations and the availability of infrastructure. Collectively, the results enrich the Diffusion of Innovations theory and the Technology–Organization–Environment framework by incorporating a socio-cultural perspective, while also emphasizing the crucial role of MSMEs’ dynamic capabilities in navigating change. The study’s implications underscore the importance of community-based policies, locally tailored assistance programs, and more equitable and inclusive interventions by digital platforms. For future research, it is recommended to extend the analysis to rural areas and adopt a longitudinal approach to capture the dynamics of digital transformation over a longer period of time.